Law Enforcement against Cybercrime in Banking in the Form of Theft of Customer Data - Bintara Sura Priambada; Ashinta Sekar Bidari; Elisa Putri Oktaviani (Budapest International Research and Critics University, 2022)
Cybercrime has various types, one of which is phishing. A phishing attack is a cybercrime in which users are tricked into sharing their personal data, such as credit card details, teller machines card details, passwords, and giving hackers access to their device, often without realizing it. Basically phishing is an infection that attacks a computer, cellphone or other device by tricking someone into downloading it. The type of research used is empirical legal research. The technique used is interview technique and document study. Analysis of the data used is qualitative data analysis. The results of the study indicate that Indonesia itself already has laws and regulations relating to electronic transactions ranging from the running of electronic transactions to the regulation of crimes, especially those related to banking such as phishing. The sentencing process for the perpetrators is intended to provide a deterrent effect and ensure the entire security of internet banking application users contained in the terms and conditions section which contains the rights and obligations of customers and banks.